HARMONI MASYARAKAT SATU DESA TIGA AGAMA DI DESA PABIAN, KECAMATAN KOTA, KABUPATEN SUMENEP, MADURA (Harmoni, 2014)
Tolerance and harmony has always been the basis for a society with religious diversity; this is especially true because religion is a way of life or a divine source of justice, truth and moral values. As a result, humans will always refer to and require religion. The community of Pabian village, Kalianget Sub Regency, Sumenep is a village located on the Eastern end of Madura Island with high levels of religious plurality. It is marked by the presence of three types of places of worship, including mosques, temples and churches. These places of worship are located very closely in distance, without conflict between the followers of each respective religions. The people visit each other, have social dialogues and participate in social activities together, resulting in a portrait of a religiously harmonious society throughout the history of the community.
Keywords: Harmony; Religion; Social Interaction; Harmoni; Agama; Interaksi Sosial